Pengaruh Harga, Kualitas produk dan Pelayanan Terhadap Keputusan Pembelian Konsumen Warung Sayur Kita Jaten - Febi Permatasari; Ari Susanti (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of price, product quality, and service quality on consumer purchasing decisions at Warung Sayur Kita Jaten. The background of the study is based on the important role of MSMEs in the fresh food retail sector in retaining consumers amidst competition with modern minimarkets. The method used is a quantitative approach with data collection techniques through distributing questionnaires to 85 respondents. Data were analyzed using instrument quality tests, classical assumption tests, and multiple linear regression with the help of SPSS 25. The results of the study indicate that price and service quality have a positive and significant effect on purchasing decisions. Meanwhile, product quality has a positive but insignificant effect. Simultaneously, the three variables are able to explain 45.8% of the variation in purchasing decisions, while the remainder is influenced by other factors outside the research model. These findings indicate that establishing a competitive pricing strategy and improving service quality need to be a priority in maintaining and improving consumer purchasing decisions.